Algunos aspectos útiles en la diagnosis de tres especies del género Eleocharis R. Brown (Cyperaceae) - Zavaro Pérez, Carlos Alberto (1993)
The taxonomical limits of the aquatic species Eleocharis interstincta, E. rtodulosa and E. elegans are established by a clustering method. These species are sometimes confused in Cuban herbaria, so the meristic value of used characters in their diagnosis and the kind of heredity that they present are also show.